2011
DOI: 10.4238/2011.october.31.16
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis as a tool for discriminating an interfamily hybrid between olive flounder and starry flounder

Abstract: ABSTRACT. An interspecific artificial hybrid was produced between two economically important aquaculture flatfish: olive flounder (Paralichthys olivaceus) and starry flounder (P. stellatus). This hybrid displays the rapid growth characteristic of the former and tolerance to low temperatures and low salinity of the latter, but the genetics of inheritance in this hybrid have not been elucidated. Polymorphic microsatellite markers developed for P. olivaceus and P. stellatus were tested to determine if these marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…To reduce the time and cost of MS marker development, pre-existing markers from related species have been applied to the study of many animal, fungus, plant and fish species [33,34]. Moreover, cross-species markers can be used for the identification of invading species and the identification of parental origin in hybrid fish [35]. Although the cross-species transferability of MS markers is unevenly distributed among taxa, over 40% and 25% of polymorphic marker transfers have been observed in fish of different genera within the same family, and of families within same order, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the time and cost of MS marker development, pre-existing markers from related species have been applied to the study of many animal, fungus, plant and fish species [33,34]. Moreover, cross-species markers can be used for the identification of invading species and the identification of parental origin in hybrid fish [35]. Although the cross-species transferability of MS markers is unevenly distributed among taxa, over 40% and 25% of polymorphic marker transfers have been observed in fish of different genera within the same family, and of families within same order, respectively [33].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, genetic studies on starry flounder with microsatellite DNA markers are very rare with only one recent report on the development of microsatellites as a tool for discriminating a hybrid between olive flounder and starry flounder [14]. No detailed information is available to date on the genetic diversity of wild and cultured stocks of starry flounder.…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellites have been used to monitor genetic differences between hatchery stocks and wild populations in various fish species [11–13]. However, despite the importance of starry flounder for commercial aquaculture in Korea, there are only a limited number of MS markers available [14]. Furthermore, no study has focused on the genetic variability and population structure of this species.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the commercial strain RT-201 artificially challenged with IPN virus showed a mortality of 4.3%, whereas the highly sensitive controls reached 96.1%. In carps, SchĂ€perclaus [6] found resistance to the dropsy disease, selected lines suffering low mortality (11.5%) well below the unselected ones (57%).…”
Section: Introductionmentioning
confidence: 99%